Law Enforcement in the Protection of Children Victims of Online Child Grooming Cyberspace during the Covid-19 Pandemic - Rahmanati, Zulfa; Priyono, Djoko; Azizah, Nita Anisatul (GMPI Conference Series, 2023)
Information-based technology is one form of the era that is always there and provides benefits, namely facilitating the activities of all levels of society, including children. Internet or cyberspace is another name for information-based technology, the reach of the internet itself is wide, and therefore even minors can access it. Child grooming is a type of crime that is either the result of the expansion of cyber-crime grooming or an approach to deception. The mode used by the perpetrator in carrying out grooming is by starting to build a relationship with the victim, then creating the victim's trust in the perpetrator, the birth of the victim's trust in the perpetrator because of the emotional relationship that exists between the victim and the perpetrator. This study wants to analyze how the practice of sexual crimes during the covid -19 pandemic in Indonesia and how the role of the ITE Law in protecting children as victims of crime during the covid-19 pandemic. The method used by the author is juridical-normative. The results obtained are that the practice of child grooming crimes during the COVID- 19 pandemic in Indonesia tends to increase, this is due to the intensity of using gadgets on children more than before the pandemic, and this is due to the government's policy, namely distance learning.